(untitled) (Research, Society and Development, 2022)
Bioactivators can provide greater P availability to plants. The objective of this study was to evaluate the response of the use of soil and plant bioactivator and phosphate fertilization on soybean yield characteristics. The design was in randomized blocks, with four replications, in a factorial scheme (5x6), being the first factor constituted by the combination of doses of triple superphosphate plus doses of the soil bioactivator (100% SFT with 0% BS; 75% of SFT with 25% BS; 50% of SFT with 50% of BS; 25% of SFT with 75% of BS and 0% of SFT with 100% of BS) and the second factor constituted of 6 doses of the plant bioactivator (0, 75, 150, 225, 300 and 375 g ha-1). The source of phosphate fertilizer was triple superphosphate. The soil bioactivator was applied 10 days before sowing. In the V4 and R1 stages, the plant bioactivator was applied. The characteristics evaluated were: number of grains per pod, number of pods per plant, plant height, height of insertion of the first pod, thousand grain weight and grain yield. There were no satisfactory responses to the use of foliar bioactivator in soybean plants. The use of 100% of the triple super phosphate was always the statistical group with the best means for the characteristics of height of insertion of the first pod, number of pods per plant, number of grains per pod, weight of one thousand grains and grain yield. The use of soil bioactivator can contribute to the reduction of mineral P doses in order to optimize crop production costs.